Prognostic value of lactate dehydrogenase to albumin ratio (LAR) in patients with resectable esophageal squamous cell carcinoma - Feng, Ji-Feng (Cancer Manag Res, 2019)
BACKGROUND: We firstly identified a combination of lactate dehydrogenase (LDH) along with albumin (ALB), which was defined as LAR (LDH/ALB ratio). The purpose of our study here was initially to explore the prognostic role of LAR in patients with esophageal squamous cell carcinoma (ESCC) undergoing esophagectomy. PATIENTS AND METHODS: A retrospective study was conducted including 346 resectable ESCC patients. Patients who received curative surgery without any neoadjuvant therapy were included in the current study. The X-tile program was performed to calculate the optimal cut-off values for LDH, ALB and LAR. The Kaplan-Meier methods, Cox regression univariate and multivariate analyses were utilized to analyze the prognostic factors for cancer-specific survival (CSS). RESULTS: There were 76 (22.0%) women and 270 (78.0%) men in all 346 patients. The mean value for serum LDH, ALB and LAR were 180±62 U/L (range 28–473 U/L), 40.3±5.3 g/L (range 26.6–52.4 g/L) and 4.6±1.8 (range 0.64–14.97), respectively. According to the X-tile program, the optimum cut-off points were 220 (U/L), 40.5 (g/L), and 5.5 for LDH, ALB, and LAR, respectively. The 5-year CSS was 31.8%. Patients with a high level of LAR (>5.5) were associated with poor CSS (13.3% vs 38.3%, P<0.001). Multivariate analyses revealed that LAR was an independent predictor in resectable ESCC patients (P=0.038). CONCLUSION: Our retrospective observations indicate that LAR is a useful potential prognostic biomarker in resectable ESCC patients who received curative surgery without any neoadjuvant therapy with the optimal cut-off value of 5.5.